EVALUASI LAYANAN KINERJA DOSEN BERBASIS SERVQUAL, CSI DAN IPA PADA POLITEKNIK NEGERI SEMARANG - Wakhid Rokhayadi; Aji Supriyanto (LPPM Universitas Abdurrab, 2026)
This research aims to evaluate the service quality of lecturer performance in the Electronics Study Program at Semarang State Polytechnic using the SERVQUAL approach, Customer Satisfaction Index (CSI), and Importance-Performance Analysis (IPA). A total of 8,131 student responses covering 124 courses and 26 lecturers were analyzed based on the five SERVQUAL dimensions: Tangible, Reliability, Responsiveness, Assurance, and Empathy. The analysis results indicate that all dimensions have negative gap scores between student perceptions and expectations, meaning the service level received is still below expectations. The Tangible dimension recorded the largest gap (-0.99), followed by Reliability and Responsiveness, which also showed relatively low scores (-0.96). A CSI value of 80.8% indicates a high level of student satisfaction. However, the IPA mapping reveals that several indicators still require attention and priority improvement, particularly concerning physical facilities and the reliability of the learning process. These findings contribute to the development of performance-based academic service improvement strategies through an integrated quantitative evaluation model. The key strategic implication of this paradoxical finding is that, although students express satisfaction (high CSI), the existence of negative gaps and priority areas in the IPA indicates that focused service quality improvements are still necessary to transform this basic satisfaction into deeper loyalty and more sustainable academic excellence.